Tropical Agrotech / Dalilah Rosdin ... [et al.] - Rosdin, Dalilah; Abd Majid, Sanaria; Hinjam, Aidil Izan; Mohd Abdul, Mohd Shahrezal (2011)
This business plan is for tropical agrotech fresh fish and chilies, a new farming and plantation business located at Kampung Sembirai which have suitable place for farming and plantation. Tropical agrotech freshwater fish and chilies emphasis the fish farming and chilies hydroponic plantation. In Sabah, freshwater fish fanning and chilies hydroponic plantation is very limited because they do not have braveness to enter this business and because the limited number of farmers in farming the freshwater fish and chilies hydroponic plantation we decide to start our business as a fresh catfish and chilies supplier. The market can be segmented into several distinct groups that it aims to target. The first group is restaurant especially the restaurant that wants to buy freshwater fish and chilies. The second groups is trader that sell the freshwater fish and chilies at market place, other then that our product also will be taken by the MARA and FAMA. The third group is hotel, catering, supermarket such as Giant, Jusco and many more. In addition we also supply freshwater and chilies to the factory food such as frozen fish or sardine and many more. Tropical agrotech fresh fish and chilies have assembled a strong management team. Dalilah binti Rosdin will the general manager and also as marketing manager which will be arranging the entire marketing project to introduce our business to the public. Sanaria binti Abdul Majid will be responsible for all the operation process from raw material to customer or end users. Aidil Izan bin Hinjam will be responsible for all finance and accounting function. Mohd Shahrezal bin Abdul will be in charge the administration which responsible to control all the activity outside and will act as a public relation to deal with the supplier Our business will be set as a partnership business. We all agree to undertake a joint business and jointly own the business and will carry out the business, share the capital, and profits: All of us will contribute RM 20 000 each except the Manager that will add a lorry to the business. The amount of contribution will be RM 100 000 with a Van. Other resources of capital will be from the bank. We will loan 70% of our cost to begin this business.